ETIKA BELAJAR DALAM AL-QURAN: (Studi Analisis Surat Al-Kahfi Ayat 66-78) - Muzakki, Zubairi; Illahi, Nur; Muljawan, Asep (STAI Asy-Syukriyyah, 2022)
Rasulullah SAW in spreading the teachings of Islam is full of gentleness, what he conveys is always a good example for his people. He is a successful leader in leading and spreading the understanding of the Islamic religion, so that all mankind can follow what he teaches. Likewise, when the prophet Khidr taught sciences that were not understood by the prophet Moses. Likewise, the prophet Moses can also be a lesson for all of us to seek knowledge. Ethics is very important for every student of knowledge as Allah has immortalized in Surah al-Kahf verses 66-78. The author tries to research and describe